Fluoride and the internet: an assessment of online information available to the public - Narmin Mammadli; Meltem Bakkal; Pınar Kınay Taran (Acta Odontologica Turcica, 2022)
Objective: Obtaining information online in health-related issues is becoming increasingly important among patients and parents. Parents are concerned about their children's fluoride use and tend to search on the internet. In this regard, the aim of this study is to assess the reliability, quality, accessibility, and readability of websites giving information on fluoride treatment. Materials and Method: Two search terms, “fluoride treatment for kids” and “is fluoride varnish safe?”, were entered into the search engines of both Google and Yahoo, and the first 50 websites were saved. After excluding duplicate sites, promotional product sites, blogs/forums, news and articles, the remaining websites were evaluated. The DISCERN and LIDA tools were used to assess reliability, quality, and usability of websites. The accessibility of websites was assessed with AChecker tool while the readability was assessed with FRES instrument. Results: Of the 200 websites saved, 94 were suitable for inclusion. The mean total DISCERN score was 53±11.2 of a possible total of 80 (66%). With the LIDA instrument, the average score for reliability was 11.8±3.9 of a possible total of 27 (43%) while the average score for usability was 31.2±7 of a possible total of 54 (58%). The mean total AChecker score was 21.8±37 and the mean FRES score was 57.7± 11.6 (of a possible total of 100) indicating a level of fairly difficult to read. Conclusion: Information about fluoride on the internet is easily accessible although the reliability and quality were highly variable. The readability of websites should be improved to be more understandable.